Anti-cancer activities of Thymoquinone, constituents of Nigella sativa against oral cancer cell lines - Arief Ichwan, Solachuddin Jauhari; Taher, Muhammad; Masa-Aki , Ikeda; Z. L, Abdullah; M.T, Junaidi (2010)
Objectives: The aims of this study were to investigate and determine anti-cancer potential of Thymoquinone (TQ), a major component of Nigella Sativa seeds against cell lines derived from oral cavity carcinoma. Methods: Three human cancer cell lines derived from oral cavity, Ca922, HSC-2 and HSC-3 were used. HCT116 (human colorectal carcinoma) cells were also used as the positive control. The cells were exposed to TQ solution at different concentrations and then analyzed after certain culture periods (12 and 24 hours). Cytotoxic activity was quantified by MTT assay. Apoptosis (programmed cell death) induction was detected by DNA Fragmentation assay. Wound-healing migration assay (Scratch assay) was performed to determine cells migration. Results: TQ dose- and time-dependently reduced the viability of Ca922, HSC-2 and HSC-3 cells. TQ treatment at 20 μM was sufficient to inhibit cancer cell migration after 12 hours. Moreover, DNA fragmentation assay shows that TQ treatment induced apoptosis in all of cell lines tested. Conclusions: TQ exhibits anti-cancer activities against oral cancer cell lines. This study suggests the potential benefit of TQ as a natural chemotherapeutic agent for oral cancer treatment.